2023
DOI: 10.1002/cam4.6223
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of Lynch syndrome, BRAFV600E, and RAS mutational status in dMMR/MSI‐H metastatic colorectal cancer in a pooled analysis of Dutch and French cohorts

Abstract: BackgroundCurrent knowledge on prognostic biomarkers (especially BRAFV600E/RAS mutations) in metastatic colorectal cancer (mCRC) is mainly based on mCRC patients with proficient mismatch repair (pMMR) tumors. It is uncertain whether these biomarkers have the same prognostic value in mCRC patients with deficient mismatch repair (dMMR) tumors.MethodsThis observational cohort study combined a population‐based Dutch cohort (2014–2019) and a large French multicenter cohort (2007–2017). All mCRC patients with a hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…[ 34 ] However, our finding is inconsistent with this report. Recently, a study reported that Lynch dMMR/MSI-H tumors more often harbored a RAS mutation (65%), [ 35 ] suggesting that the results observed in our study may be due to a potentially higher proportion of Lynch syndrome patients in the MSI-H group. The MMR gene status detection is crucial for the diagnosis of Lynch syndrome.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…[ 34 ] However, our finding is inconsistent with this report. Recently, a study reported that Lynch dMMR/MSI-H tumors more often harbored a RAS mutation (65%), [ 35 ] suggesting that the results observed in our study may be due to a potentially higher proportion of Lynch syndrome patients in the MSI-H group. The MMR gene status detection is crucial for the diagnosis of Lynch syndrome.…”
Section: Discussionmentioning
confidence: 47%
“…The mutation rate of 28% closely matches the results of the aforementioned study, where the A146 mutation rate reached 20% in the MSI-H group. [ 35 ] The high frequency of K117N/A146V/A146P/A146T mutations in the MSI-H group of our study may be one of the critical factors contributing to the overall increased KRAS mutation rate. Overall, it suggests that the exact relationship between KRAS mutations and MSI in the real world still requires further research to be determined.…”
Section: Discussionmentioning
confidence: 90%